PSVII-12 The Effect of a Linear Relationship between the Dose of Peanut Skin Supplementation and Animal Performance, Ruminal Fermentation, Blood Metabolites, and Carcass Traits in Meat Goats Confined Indoor. (7th December 2018) - Abrahamsen, F; Min, B; Gurung, N
Abstract: The aim of this study was to determine the effects of an either linear dose level (0–30% DM) or high concentration of peanut skin (PS; 70%) supplementation on animal performance, rumen fermentation, blood metabolites, internal parasites load (FEC), and carcass traits in meat goats under confined condition. Thirty Kiko-crossbreed male goats were randomly assigned to one of five treatments (n = 6); 1) 30% Bermudagrass hay and 70% grain mix (control), 2) 15% PS and 85% grain mix, 3) 30% PS and 70% grain mix, 4) 70% PS and 30% grain mix with 15 days feeding, and 5) 70% PS and 30% grain mix with 30 days feeding, and then back to control diet, respectively. Animals were each artificially infected with 5000 of third stage larvae of the Haemonchus contortus 6 wks. before the initiation of the experiment. The BW was monitored weekly while FEC, blood metabolites, and rumen The BW volatile fatty acid concentrations were measured at the end of trial. Following the feeding trial, animals were transported to the Fort Valley State University, GA for slaughtering, abomasum sampling (adult worm counts), and carcass evaluation. The results showed that BW, carcass traits and meat colors were not affected by PS supplementation, while ADG (P<0.01), blood glucose (P<0.001), P (P<0.03), and cholesterol levels (P<0.001) increased significantly with increasing PS supplementation. Similarly, there was a linear (P<0.01) reduction in rumen acetate/propionate ratios, rumen ammonia level, FEC, and H. contortus, with increased level of PS supplementation. At the 70% PS supplementation, the FEC (P<0.05) and adult worm counts (P<0.001) were also reduced compared to the control diet, but ADG was lower (P<0.05) compared to other treatments. This study shows that PS supplementation up to 30% in the diet can improve animal performance, rumen fermentation while reducing gastrointestinal parasites infection in meat goats.